1
$\begingroup$

I'm solving the following differential equation with a Laplace Transform:

$$x″+ 9x = \cos(t) + \delta(t-\pi)$$

The initial conditions are that x(0) and x'(0) are equal to 0.

After after the transform, we obtain:

$$F(S) = \frac{S}{(S^2+9)[(S^2+1)+9]} + \frac{e^{-\pi\cdot t}}{S^2+9}$$

The problem is that there are two unique irreducible quadratic factors in the denominator of that first term: therefore I cannot seem to find a way to simplify this to find equivalent components which would make the inverse transform easier. How do I find the inverse of that first term?

$$\frac{S}{(S^2+9)[(S^2+1)+9]}$$

The answer includes simple cos(t) and cos(3t) terms with coefficients of $\frac{1}{8}$ and $\frac{-1}{8}$ respectively. What is the process of going from this complex laplace transform to something so simple?

$\endgroup$
5
  • $\begingroup$ You can still factor into linear factors with complex roots. Alternatively, you can find a partial fraction decomposition of the form $(AS + B)/(S^2 + 9) + (CS + D)/(S^2 + 1)$ for some $A,B,C,D$ real and use facts about Laplace transforms of $\sin$ and $\cos$ $\endgroup$
    – Jane Doé
    May 2, 2019 at 1:18
  • $\begingroup$ Thank you- I will try solving this way. $\endgroup$ May 2, 2019 at 1:24
  • $\begingroup$ The problem has changed now: there is an extra 9 in the denominator which I didn't expect: How might I approach the problem now? $\endgroup$ May 2, 2019 at 1:47
  • $\begingroup$ The way you wrote it, you can rewrite $(S^2+1)+9 = S^2 + 10$. If you mean $(S+1)^2 + 9$, you can look at Laplace transforms of functions of the form $e^{at}\cos(bt)$ and $e^{bt}\sin(bt)$. $\endgroup$
    – Jane Doé
    May 2, 2019 at 2:07
  • $\begingroup$ Thank you- I'll try this. $\endgroup$ May 2, 2019 at 2:34

2 Answers 2

1
$\begingroup$

Alternative Method

$$ F(s)=\underbrace{\frac{s}{(s^2+1)(s^2+9)}}_{\mathbf{(I)}}+\underbrace{\frac{e^{-\pi s}}{s^2+9}}_{\mathbf{(II)}} $$

Alternative (and fast) method for $\mathbf{(I)}$:


We can also decompose $\mathbf{(I)}$ using partial fractions by the following way:

$$ \frac{s}{(s^2+1)(s^2+9)}\equiv\frac{Es+F}{s^2+1}+\frac{Gs+H}{s^2+9} $$ Finding the constants of partial fractions decomposition $$ \frac{s}{(s^2+1)(s^2+9)}\equiv\frac{(Es+F)\cdot(s^2+9)+(Gs+H)\cdot(s^2+1)}{(s^2+1)(s^2+9)} $$

Now, working only with the numerators: $$s\equiv (E+G)\cdot s^3+(F+H)\cdot s^2+(9E+G)\cdot s+(9F+H)$$ Thus, we can find $E$, $F$, $G$ and $H$ solving the following system of equations:

$$\mbox{$ \begin{cases} \begin{alignat}{1} E+G&=0 \\F+H&=0 \\9E+G&=1 \\9F+H&=0 \end{alignat} \end{cases} $} \implies \mbox{$ \begin{cases} \begin{alignat}{1} E&=1/8 \\F&=0 \\G&=-1/8 \\H&=0 \end{alignat} \end{cases} $} $$

Thus, we get: $$ \frac{s}{(s^2+1)(s^2+9)}\equiv \frac{s}{8\cdot(s^2+1)}-\frac{s}{8\cdot(s^2+9)} $$


Now we can apply the Inverse Laplace Transform:

Remember that the Laplace transform of cosine function is: $$ \cos(\omega t) \iff \frac{s}{s^2+\omega^2} $$ So, we have:

$$ \begin{alignat}{1} \mathscr{L}^{-1}\left[\frac{s}{8\cdot(s^2+1)}-\frac{s}{8\cdot(s^2+9)}\right]&=\frac 1 8 \,\mathscr{L}^{-1}\left[\frac{s}{s^2+1^2}\right]-\frac 1 8 \,\mathscr{L}^{-1}\left[\frac{s}{s^2+3^2}\right] \\&=\frac{1}{8}\left[cos(t)-cos(3t)\right] \end{alignat} $$


Same answer here

$$ \bbox[5px,border:1.1px solid black] { x(t)=\frac{1}{8}\left[cos(t)-cos(3t)\right]-\frac 1 3\sin(3t)\cdot\operatorname{H}(t-\pi) } $$

$\endgroup$
1
$\begingroup$

Laplace Transform

We have, as pointed in the question, the following equation: $$x''(t)+ 9x(t) = \cos(t) + \delta(t-\pi)$$ With $x(0)=0$ and $x'(0)=0$. So applying the Laplace Transform: $$ \require{cancel} \begin{alignat}{1} \mathscr{L}\left[x''(t)+9x(t)\right]&=\mathscr{L}\left[ \cos(t) + \delta(t-\pi)\right] \\ s^2F(s)-s\cancelto{0}{f(0)}-\cancelto{0}{f'(0)}+9F(s)&=\frac{s}{s^2+1^2}+e^{-\pi s}\cdot1 \\s^2F(s)+9F(s)&=\frac{s}{s^2+1}+e^{-\pi s} \\(s^2+9)\cdot F(s)&=\frac{s+(s^2+1) e^{-\pi s}}{s^2+1} \end{alignat}$$

So, after the transform, we obtain: $$ \bbox[5px,border:1.1px solid black] { F(s)=\frac{s+(s^2+1) e^{-\pi s}}{(s^2+1)(s^2+9)}=\frac{s}{(s^2+1)(s^2+9)}+\frac{e^{-\pi s}}{s^2+9} } $$


Your transform is wrong in two places: $$F(S) = \frac{S}{(S^2+9)[(S^2+1) \bbox[yellow,4px,border:1.5px solid red]{+9}\,]} + \frac{e^{-\pi\cdot \, \bbox[yellow,4px,border:1.5px solid red]t}}{S^2+9}$$


Inverse Laplace Transform

Now, we have two parts in the right side to apply the Inverse Laplace Transform: $$ F(s)=\underbrace{\frac{s}{(s^2+1)(s^2+9)}}_{\mathbf{(I)}}+\underbrace{\frac{e^{-\pi s}}{s^2+9}}_{\mathbf{(II)}} $$

For $\mathbf{(I)}$, we need to decompose it via partial fractions first:


$\,\,\,\,\,\,\,\mathbf{1.}$ Finding zeros of $s^2+1$ and $s^2+9$ $$\begin{alignat}{1} s^2+1=0 &\iff s=\pm\sqrt{-1}=\pm \,i \\s^2+9=0 &\iff s=\pm\sqrt{-3}=\pm \,3i \end{alignat} $$ Now that we know that $s^2+1=(s+i)\cdot(s-i)$ and $s^2+9=(s+3i)\cdot(s-3i)$, we can proceed the decomposition.

$\,\,\,\,\,\,\,\mathbf{2.}$ Finding the constants of partial fractions decomposition $$ \frac{s}{(s^2+1)(s^2+9)}\equiv\frac{A}{s+i}+\frac{B}{s-i}+\frac{C}{s+3i}+\frac{D}{s-3i}\equiv \\\equiv\frac{A\cdot (s-i)(s^2+9)+B\cdot(s+i)(s^2+9)+C\cdot (s^2+1)(s-3i)+D\cdot (s^2+1)(s+3i)}{(s^2+1)(s^2+9)} $$ Now, working only with the numerators: $$s\equiv A\cdot (s-i)(s^2+9)+B\cdot(s+i)(s^2+9)+C\cdot (s^2+1)(s-3i)+D\cdot (s^2+1)(s+3i)$$ Since we're dealing with an identity (i.e. valid for every $s$), we can arbitrarily chose values and put them into the identity to find $A$, $B$, $C$ and $D$:

$$ \begin{cases} \begin{alignat}{1} s=-i &\implies A=\frac{1}{16} \\ s=i &\implies B=\frac{1}{16} \\ s=-3i &\implies C=-\frac{1}{16} \\ s=3i &\implies D=-\frac{1}{16} \end{alignat} \end{cases} $$ Thus, we get: $$ \frac{s}{(s^2+1)(s^2+9)}\equiv\frac{1/16}{s+i}+\frac{1/16}{s-i}-\frac{1/16}{s+3i}-\frac{1/16}{s-3i} $$


Now we can apply the Inverse Laplace Transform: $$ \mathscr{L}^{-1}\left[\frac{1/16}{s+i}+\frac{1/16}{s-i}-\frac{1/16}{s+3i}-\frac{1/16}{s-3i}\right]= \\=\frac{1}{16}\,\mathscr{L}^{-1}\left[\frac{1}{s+i}\right]+\frac{1}{16}\,\mathscr{L}^{-1}\left[\frac{1}{s-i}\right]-\frac{1}{16}\,\mathscr{L}^{-1}\left[\frac{1}{s+3i}\right]-\frac{1}{16}\,\mathscr{L}^{-1}\left[\frac{1}{s-3i}\right] $$ Remembering that the Laplace transform of exponential function is: $$ e^{-at} \iff \frac{1}{s+a} $$ We finally have: $$ \mathscr{L}^{-1}\left[\frac{1/16}{s+i}+\frac{1/16}{s-i}-\frac{1/16}{s+3i}-\frac{1/16}{s-3i}\right]= \frac{1}{16}e^{-i\cdot t}+\frac{1}{16}e^{i\cdot t}-\frac{1}{16}e^{-3i\cdot t}-\frac{1}{16}e^{3i\cdot t} $$ Using Euler's identity ($e^{i\cdot\theta}\equiv \cos\theta+i\sin\theta)$, we can write the above result in terms of sines and cosines: $$ \begin{cases} \begin{alignat}{1} e^{-i\cdot t}&=\cos(t)-i\sin(t) \\e^{i\cdot t}&=\cos(t)+i\sin(t) \\e^{-3i\cdot t}&=\cos(3t)-i\sin(3t) \\e^{3i\cdot t}&=\cos(3t)+i\sin(3t) \end{alignat} \end{cases} \implies \frac{1}{16}\left(e^{-i\cdot t}+e^{i\cdot t}-e^{-3i\cdot t}-e^{3i\cdot t}\right)=\frac{1}{8}\left[cos(t)-cos(3t)\right] $$


For $\mathbf{(II)}$, we need to use the following:

$\,\,\,\,\,\,\,\mathbf{1.}$ Laplace time shift property $$ f(t-a) \cdot \operatorname{H}(t-a) \iff e^{-a s}\cdot F(s) $$ (where $\operatorname{H}(t)$ is the Heaviside step function)

$\,\,\,\,\,\,\,\mathbf{2.}$ Laplace transform of sine function $$ \sin(\omega t) \iff \frac{\omega}{s^2+\omega^2} $$

Combining these two things, we can find the Inverse Laplace Transform of $\mathbf{(II)}$:

$$ \mathscr{L}^{-1}\left[\frac{e^{-\pi s}}{s^2+9}\right]=\mathscr{L}^{-1}\left[\frac{1} {\color{red}3}\cdot\frac{\color{red}3\cdot e^{-\pi s}}{s^2+3^2}\right]=\frac 1 3 \cdot \mathscr{L}^{-1}\left[e^{-\pi s}\cdot\frac{3}{s^2+3^2}\right]=\frac 1 3\sin(3t-\pi)\cdot\operatorname{H}(t-\pi) $$


Finally, the answer:

Remembering that $\sin(3t-\pi)=-\sin(3t)$, we have: $$ \bbox[5px,border:1.1px solid black] { x(t)=\frac{1}{8}\left[cos(t)-cos(3t)\right]-\frac 1 3\sin(3t)\cdot\operatorname{H}(t-\pi) } $$

$\endgroup$
4
  • 1
    $\begingroup$ The partial fraction decomposition goes easier if you first separate the quadratic factors, treating $s^2$ like a single variable, $$\frac{1}{(s^2+1)(s^2+9)}=\frac{(s^2+9)-(s^2+1)}{8(s^2+1)(s^2+9)}=\frac1{8(s^2+1)}-\frac1{8(s^2+9)}.$$ Such an intermediate decomposition is always possible if the polynomial factors do not have common roots. As one obtains terms that have a direct inverse Laplace transform, no further factorization is necessary. $\endgroup$ May 2, 2019 at 8:28
  • $\begingroup$ @LutzL See my alternative answer below :) $\endgroup$ May 2, 2019 at 8:30
  • 1
    $\begingroup$ Brilliant. Everything I needed. Thank you! $\endgroup$ May 2, 2019 at 13:40
  • $\begingroup$ I'm glad it helped :) $\endgroup$ May 2, 2019 at 16:47

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.